Process study on composite products / Mohd Shah Rizan Abdul Hafiz and Widia Wahid - Abdul Hafiz, Mohd Shah Rizan; Wahid, Widia (Faculty of Mechanical Engineering, 2003)
Among the major developments in material in recent years are composite materials. In fact, composite are now one of the most important classes of engineered materials, because they offer several outstanding properties as compared to conventional materials. Because of that we decided to choose “The process study on Composite Product” as our project and title for our thesis. In this thesis, we describe a little bit about the company that produced product using composite materials that we had visited. This thesis also describes about the process applying composite materials in the Airbus components A300 and FRP storage tank. This FRP storage tank is manufactured using the 100% hand lay-up method of fabrication different by Airbus components, where some of its process using a machine. We also propose on some aspects that should be developed and introduced in order to improve the process involved in composite technology especially on cost. Discussion on the future of composites in Malaysia also been done to ensure people may expect how the industrial scenario going to be in few years from today.